Comparison of conventional methods with gene xpert mtb/rif assay for rapid detection of mycobacterium tuberculosis and rifampicin resistance in extra-pulmonary samples - Sanjay Avashia; Deepak Bansal; Kunal Ahuja; Vijay Agrawal (International Journal of Medical Research and Review, 2016)
Introduction: Tuberculosis (TB) is a major health problem in India. The World Health Organization has recently in 2010 endorsed the Gene Xpert MTB/RIF assay for rapid detection of smear negative and multidrug resistance tuberculosis and more recently for extra pulmonary tuberculosis.Objectives: Evaluation of role of Cartridge based nucleic acid amplification test (CBNAAT) in extra-pulmonary tuberculosis (EPTB) in comparison with Ziehl Neelsen (ZN) staining and evaluating rifampicin resistance with the same test.Materials & Methods: Extra-pulmonary samples, including pleural fluid, pus, CSF, lymph tissue & others were divided in 2 parts: one for MTB/RIF assay & other for ZN staining. Both were then compared.Results: A total of 300 extra pulmonary samples were processed in this study, which included 103 pleural fluids, 81 pus, 45 CSF, 35 Lymph node tissue, 20 ascitic fluids and 16 synovial fluid. Out of these 37% (111) patients were Gene Xpert MTB/RIF Assay positive and 36 % (40 out of 111) were ZN smear positive. M.tuberculosis was detected in 56.7% pus samples, 23.3% pleural fluid samples, 54.2% lymph node samples, 33.3 % CSF samples, 20% ascitic fluid samples and 18.7% synovial fluid samples. In this study, we found that Gene Xpert MTB/RIF assay is a rapid method for diagnosis of EPTB as compared to conventional methods along with advantage of detecting Rifampicin resistance.Conclusion: Because of its simplicity, rapidity and sensitivity, this seems to be a very novel tool for diagnosis of extra pulmonary tuberculosis from clinical samples and that it should be researched more thoroughly.